Lifetime estimation for IGBT modules in wind turbine power converter system considering ambient temperature. (October 2016) - Du, Xiong; Zhang, Jun; Li, Gaoxian; Tai, Heng-Ming; Sun, Pengju; Zhou, Luowei
Abstract: Power semiconductors in the wind turbine power converter system suffer from two-scale thermal loadings, the fundamental frequency thermal cycling caused by the output frequency of converter and the low frequency thermal cycling due to the variation of long-term wind speed. These two-scale thermal loadings introduce different consumed lifetimes. Accurate lifetime estimation in the wind power application is desired for reliability prediction and health management. This paper adopts the Bayerer lifetime model to evaluate the consumed lifetime of power semiconductors in wind power converter systems based on a numerical junction temperature calculation method. Lifetime estimation can be improved by taking into account the ambient temperature. Studies show that fluctuations of the ambient temperature increase the consumed lifetime due to the low frequency thermal cycling, but have little effect on the consumed lifetime due to the fundamental frequency thermal cycling. Our results also show that the consumed lifetime due to fundamental frequency thermal cycling mainly falls on the high wind speed area, whereas the consumed lifetime due to low frequency thermal cycling is clustered in the area due to large low frequency junction temperature fluctuations. The resulting distribution characteristics can be used in the thermal management for reliability improvement. Highlights: Incorporation of ambient temperature into the junction temperature calculation leads to more accurate lifetime estimation. Ambient temperature fluctuation has detrimental effects on the device lifetime. Consumed lifetime distribution of power devices can offer long term reference control setting for thermal management.